2021
DOI: 10.3389/fpsyg.2021.664964
|View full text |Cite
|
Sign up to set email alerts
|

Using Mindfulness to Reduce Anxiety and Depression of Patients With Fever Undergoing Screening in an Isolation Ward During the COVID-19 Outbreak

Abstract: The coronavirus disease 2019 (COVID-19) continues to spread globally. This infectious disease affects people not only physically but also psychologically. Therefore, an effective psychological intervention program needs to be developed to improve the psychological condition of patients screened for fever during this period. This study aimed to investigate the effect of a brief mindfulness intervention on patients with suspected fever in a screening isolation ward awaiting results of the COVID-19 test. The Face… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…Consistent with previous studies, we also found that the vNOTES group had shorter postoperative exhaust times than that of the LESS group (43,44), which may be due to the following reasons. First, vNOTES surgery is performed in the pelvis and has little effect on the upper abdomen.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous studies, we also found that the vNOTES group had shorter postoperative exhaust times than that of the LESS group (43,44), which may be due to the following reasons. First, vNOTES surgery is performed in the pelvis and has little effect on the upper abdomen.…”
Section: Discussionsupporting
confidence: 92%
“…The use of a virtual medium to deliver guidance for mindfulness or mindful meditation is convenient and widely accessible to anyone with a smartphone [10,12,22]. Even a single session or brief intervention may provide some benefit in the reduction of stress and anxiety [51][52][53]. By using a free smartphone app, the practice of mindfulness or mindful meditation becomes accessible to anyone with a smartphone, day or night, even in the presence of isolation and lockdown measures as experienced during the COVID-19 pandemic.…”
Section: Feasibility Of Using a Virtual Medium For Delivery Of Mindfu...mentioning
confidence: 99%
“…Rapid testing, accuracy, and convenience are the key features required for fever screening ( 19 , 20 ). Compared with mercury axillary thermometers (MATs), non-contact infrared thermometers (NCITs) are more suitable for fever screening because of the rapidity and convenience ( 21 , 22 ).…”
Section: Introductionmentioning
confidence: 99%